(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This research explores the educational potential and threats to biodiversity posed by the overproduction and exploitation of butterflies in live exhibitions. Ecosystems rely on butterflies. They indicate a shift in the climate and play a crucial role in pollination. All three art, culture, and emotions involve them. Insects belonging to the lepidoptera order are useful for many reasons, including pollinating plants, spinning silk, signaling changes in the environment, and being aesthetically pleasing. Ecosystem richness and variety change over time. The variety and number of butterfly species have increased due to the growing popularity of polyculture farms and organic farming methods. A relatively new kind of zoo the butterfly house has exploded in popularity during the last three decades. As a result, a new industry known as the Butterfly House Industry (BHI) has emerged all over the world, focused on the commercial cultivation of butterfly pupae. Here we present the 174 butterfly species and subspecies from 100 genera and 8 families that have been identified so far from the Indian states of Chhattisgarh and Madhya Pradesh.